An investigation of post treatment on properties and structure of ultrahigh molecular weight polyethylene parts prepared by selective laser sintering for biomedical application. (21st February 2020) - Zhao, Yinglun; Yang, Qi; Ma, Haoyu; Wu, Pingping; Huang, Yajiang; Gong, Pengjian
Abstract : Combined with customization advantage of selective laser sintering (SLS) and excellent performance of ultrahigh molecular weight polyethylene (UHMWPE), it is possible to meet the requirements of artificial joints for biomedical application. However, high viscosity of UHMWPE melt limits the strength of UHMWPE sintered parts. Inspired from metal and ceramic materials, this work aims to improve the performance of UHMWPE parts prepared by SLS using post treatment methods, including heat treatment and hot isostatic pressure (HIP) treatment. Consequently, HIP treatment shows superiority on promoting the performance of UHMWPE sintered parts compared with heat treatment. With the condition of temperature and isostatic pressure, a novel definition of "bonding neck" is given to explain the enhancement of cohesion between each UHMWPE particle in different post treatment. Without any fortifier, the biological safety of artificial joints manufactured by SLS is further guaranteed. Under the isostatic pressure of 12 MPa and temperature of 185°C in HIP treatment, the mechanical strength, tribological performance and other properties are improved dramatically. The tensile strength of the specimen is up to 8.0 MPa, the elongation at break is 99.3%, the impact strength is 8.8 MPa, the friction coefficient is 0.11, the wear rate is 9.3 × 10 −4 mm 3 /Nm and samples do not show cytotoxicity at the same time.